The issue of the management of the city county’s income on the basis of the Świnoujście city - Bartłomiej Suchodolski; Monika Wakuła (Scientific Journal of the Military University of Land Forces, 2019)
The publication addresses the issue of financing the activities of city counties in Poland. City counties are municipalities executing county tasks based on principles under the relevant act. Their area covers territories of bigger cities. Cities entitled to the rights of a county include those which in December 31, 1998 had more than 100,000 inhabitants, those which lost their right to be the seat of a voivode-ship, unless the relevant authorities at the request of a city council refused to grant county rights to a city, and those which were given the status of a county in the first state’s administrative division into the counties. City counties constitute a specific combination of a mu-nicipality and a county, as they fulfill not only municipality tasks but also county functions. They constitute a substantial part of the struc-ture of the Polish self-governmental administration. The legislator imposed a significant number of tasks on it. Their execution requires possessing necessary funds of an adequate amount by a unit. In-comes of city counties encompass three groups – own incomes, gen-eral subsidies and grants. Due to the dual construction of city coun-ties, municipality and county incomes can be distinguished in their profit structure as well. Management of varied sources of incomes can create problems that are to be overcome by authorities of the so-called district cities. The theoretical part of the article characterizes city counties as an element of the Polish self-governmental administration. Further-more, the review of sources financing their activities is conducted, whereas the experiential part is presented in the form of the case study attempting to assess the income side of the budget of Świnoujście City.